Manajemen Laba di Industri Perbankan : Suatu Pengujian Sebelum dan Saat Covid-19 - Salmita, Dewi (Politeknik Ganesha Medan, 2024)
The Covid-19 pandemic has become one of the toughest phases for all countries whose citizens have been confirmed positive, including Indonesia. Profit management in the period before and during the Covid-19 pandemic is interesting to research because almost all industrial sectors were affected by this pandemic, including the banking industry. The aim of the research is to analyze the profit management of the banking industry listed on the Indonesia Stock Exchange and the significance of the differences before and during the Covid-19 pandemic. This research uses secondary data in the form of banking financial reports listed on the Indonesian Stock Exchange (BEI). The research years were taken from 2017-2019 for the year before the Covid-19 pandemic and 2020-2022 for the year during the Covid-19 pandemic. Financial reports are downloaded from each banking industry website. The total population in this study was 46 companies, after being eliminated using the purposive sampling method it became 43 companies. The earnings management variable is proxied by discretionary accruals (DA) which are measured using the Modified Jones Model. Hypothesis testing uses the Wilcoxon Signed Rank Test via SPSS 26 software. The research results show that there are significant differences in banking industry earnings management before and during the Covid-19 pandemic. Before the Covid-19 pandemic, banks tended to carry out earnings management by increasing the value of their reported profits, whereas during the Covid-19 pandemic, banks tended to carry out earnings management by reducing the value of their reported profits.